INFLUENCE OF PACKAGING ELEMENTS ON BRAND IMAGE AND THE BUYING DECISION TO PURCHASE JAPAN BRAND DESSERT PRODUCTS - Chokluechai, Khwannatee; Sasithanakornkaew, Saranthorn; Apisuphachok, Warapan (Journal of MCU Nakhondhat, 2024)
This study aimed to examine 1) demographic characteristics, packaging elements, brand image, and purchasing decisions; 2) differences in demographic characteristics and perceptions of packaging elements for Japanese dessert products; 3) the relationship between packaging elements and the brand image of Japanese dessert products; 4 ) the relationship between brand image and the decision to purchase Japanese dessert products; 5) the influence of packaging elements and brand image on the decision to purchase Japanese dessert products. It’s a quantitative study with a sample of 400 participants who were at least 20 years old and had experience purchasing Japanese dessert products. Data were gathered through a questionnaire, while descriptive statistics, including percentages, means, and standard deviations, were utilized to examine the results. Research hypotheses were tested with inferential statistical analysis in the form of a t - test, one - way ANOVA, correlation statistics, and multiple regression analysis. It was found that the sample’s overall opinion on packaging elements was at a high level, with a mean score of 4.09, while their image perception and purchasing decisions had total mean scores of 4.34 and 4.44, respectively. Packaging elements and brand image influenced the decision to purchase Japanese dessert products with a statistical significance level of 0.05, and the variation in purchasing decisions was 62.1%, both variables had an influence on the decision to purchase Japanese brand dessert products. Statistically significant at the 0.05 level include Packaging elements and brand image had standard regression coefficients of 0.455 and 0.400, respectively.